Application of nanotechnology in asphalt binder: A conspectus and overview - Wan Azahar, Wan Nur Aifa; Bujang, Mastura; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; A. Aziz, Md. Maniruzzaman; Ngadi, Norzita (UTM Press, 2015)
Nowadays, the nanotechnology is widely applied in pavement engineering in order to improve the properties of materials and their performance. Nanotechnology can be considered as the measurement on nanometer scale that affects the material used in pavement due to its unique characteristic. Therefore, this new technology might indirectly solve the current pavement construction problems. The application of nanotechnology in enhancing the performance of fresh bitumen in term of the longevity and durability has been proven by a lot of previous studies and researches. Literatures have been reviewed and summarized critically to give an overview about the role of nanotechnology in improving pavement material properties. There are some concerns in the application of nanotechnology that needs to be addressed regarding to the safeties of these nano-materials in term of human health.